Development of Prayer Rakaat Counter Using Piezoelectric Sensor - Decy Nataliana; Dini Fauziah; Mellynda Riska Dianti (Institut Teknologi Nasional, Bandung, 2022)
In this study, a rakaat counter tool was designed and implemented to reduce mistakes in calculating the number of rakaat during prayer. The piezoelectric is used as sensor which is placed on the top of the prayer mat. Rakaat is calculated when piezoelectric has detected twice prostration. There are four modes in this system, namely fardhu prayer with seven segment display, fardhu prayer with LED display, sunnah prayer with seven segment display, and sunnah prayer with LED display.. There is an LED indicator when the rakaat is done which should be in accordance with the prayer time using RTC. The first test of this tool was carried out with piezoelectric calibration when pressed by the load and forehead. This was accomplished to determine when piezoelectric counting proceeded as piezoelectric was connected directly to the ADC of Arduino Uno. The second test was carried out by testing the tool to be used for 3 days in 5 fardhu prayers and 1 sunnah prayer. From the results of the testing it is proven that this tool works properly, and piezoelectric can be used as a replacement button as a tool for rakaat counter.